Self-reported offending, maturational reform, and the Easterlin hypothesis - Menard, Scott W. (Journal of quantitative criminology, 1990)
The maturational reform hypothesis and the Easterlin cohort size hypothesis are used to specify models in which age, period, and cohort effects on self-reported crime and delinquency are estimated. Curvilinear effects, logarithmic transformations, and the distinction between prevalence and frequency of offending are considered. The maturational reform hypothesis is supported for general delinquency but not for serious (Index) delinquency, for which there appears to be a steady decline in the behavior with age. The Easterlin hypothesis is supported for both general and Index delinquency. Theoretical, methodological, and substantive implications of the results are discussed.